From acidophilic to ornithogenic: microbial community dynamics in moss banks altered by gentoo penguins - Prekrasna-Kviatkovska, Yevheniia; Parnikoza, Ivan; Yerkhova, Anna; Stelmakh, Olesia; Pavlovska, Mariia; Dzyndra, Marta; Yarovyi, Oleksandr; Dykyi, Evgen (Frontiers in Microbiology, 2024)
The study explores the indirect impact of climate change driven by gentoo's penguin colonization pressure on the microbial communities of moss banks formed by Tall moss turf subformation in central maritime Antarctica. Microbial communities and chemical composition of the differently affected moss banks (Unaffected, Impacted and Desolated) located on Galindez Island and Сape Tuxen on the mainland of Kyiv Peninsula were analyzed. The native microbiota of the moss banks' peat was analyzed for the first time, revealing a predominant presence of Acidobacteria (32.2±14.4%), followed by Actinobacteria (15.1±4.0%) and Alphaproteobacteria (9.7±4.1%). Penguin colonization and subsequent desolation of moss banks resulted in an increase in peat pH (from 4.7±0.05 to 7.2±0.6) and elevated concentrations of soluble nitrogen (from 1.8±0.4 to 46.9±2.1 DIN, mg/kg) and soluble phosphorus compounds (from 3.6±2.6 to 20.0±1.8 DIP, mg/kg). The contrasting composition of peat and penguin feces led to the elimination of the initial peat microbiota, with an increase in Betaproteobacteria (from 1.3±0.8% to 30.5±23%) and Bacteroidota (from 5.5±3.7% to 19.0±3.7%) proportional to the intensity of penguins' impact, accompanied by a decrease in community diversity. Microbial taxa associated with birds' guts, such as Gottschalkia and Tissierella, emerged in Impacted and Desolated moss banks, along with bacteria likely benefiting from eutrophication. The changes in the functional capacity of the penguin-affected peat microbial communities were also detected. The nitrogen-cycling genes that regulate the conversion of urea into ammonia, nitrite oxide, and nitrate oxide (ureC, amoA, nirS, nosZ, nxrB) had elevated copy numbers in the affected peat. Desolated peat samples exhibit the highest nitrogen-cycle gene numbers, PAGE \* Arabic \* MERGEFORMAT significantly differing from Unaffected peat (p < 0.05). In conclusion, the expansion of gentoo penguins induced by climate change led to the replacement of acidophilic microbiomes associated with moss banks, shaping a new microbial community influenced by penguin guano's chemical and microbial composition.